2021
DOI: 10.3390/su13158182
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring System for Tracking a PV Generator in an Experimental Smart Microgrid: An Open-Source Solution

Abstract: Smart grids and smart microgrids (SMGs) require proper monitoring for their operation. To this end, measuring, data acquisition, and storage, as well as remote online visualization of real-time information, must be performed using suitable equipment. An experimental SMG is being deployed that combines photovoltaics and the energy carrier hydrogen through the interconnection of photovoltaic panels, electrolyser, fuel cell, and load around a voltage bus powered by a lithium battery. This paper presents a monitor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 43 publications
0
18
0
Order By: Relevance
“…Photovoltaic (PV) technology is one of the most widespread renewable energy sources (RES) [1,2] and contributes to reducing greenhouse gas emissions and fighting against climate change [3]. In intelligent energy facilities conceived under the paradigm of smart grids and microgrids, PV generators are commonly the main source of renewable energy [4]. In these facilities, PV can be combined with other equipment for energy production and consumption such as wind turbines, batteries, and hydrogen-related devices (fuel cells and electrolyzers).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Photovoltaic (PV) technology is one of the most widespread renewable energy sources (RES) [1,2] and contributes to reducing greenhouse gas emissions and fighting against climate change [3]. In intelligent energy facilities conceived under the paradigm of smart grids and microgrids, PV generators are commonly the main source of renewable energy [4]. In these facilities, PV can be combined with other equipment for energy production and consumption such as wind turbines, batteries, and hydrogen-related devices (fuel cells and electrolyzers).…”
Section: Introductionmentioning
confidence: 99%
“…For example, Arduino is used in [25,26] to sense the temperature of PV modules. With higher computation capabilities, the RPi microprocessor is used to implement monitoring systems for PV-based microgrids in [4,27,28] and for PV plants in [5,29,30].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The authors reported improved system performance in transmissions for a naval unit. The authors reported improved system performance in terms of reduced noise and vibrations, increased efficiency of lubrication, reduced consumption, installation, and maintenance cost of the entire system [6,7]. In another study, Giallanza et al [8] used IR 4.0-based technologies to develop a smart shipyard for testing elevated power thrusters before installing them on high-speed crafts.…”
Section: Introductionmentioning
confidence: 99%